High-thermal-conductivity aluminum alloy composite material and preparation method thereof
By introducing graphite sheets and rare earth elements into the aluminum alloy and adopting a specific process treatment, the problem of low thermal conductivity of traditional aluminum alloys is solved, and a combination of high thermal conductivity and excellent mechanical properties is achieved.
Patent Information
- Application Number
- CN202411550344.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional aluminum alloys have low thermal conductivity, which is difficult to meet the requirements of high thermal conductivity, and the challenge of maintaining mechanical properties while improving thermal conductivity.
By introducing graphite sheets into the aluminum alloy as a reinforcement material, combined with the addition of rare earth elements, mechanical mixing is performed by ball milling, followed by melt casting and semi-solid forming processes, and heat treatment is performed to improve the thermal conductivity and mechanical properties of the material.
The thermal conductivity of aluminum alloy composite materials has been significantly improved, increasing by about 25%-30%, while enhancing the tensile strength and yield strength, improving the comprehensive mechanical properties of the material.
Smart Images

Figure BDA0005114914850000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of aluminum alloy composite materials, and more particularly to a high thermal conductivity aluminum alloy composite material and a preparation method thereof. Background Art
[0002] With the rapid development of modern industrial technology, the demand for efficient heat dissipation materials is increasing, especially in electronic, power and communication equipment, where high power density components have put forward higher requirements for heat dissipation materials. Aluminum alloys are widely used in these fields due to their excellent comprehensive properties, such as light weight, high strength, good thermal conductivity and easy processing. However, the thermal conductivity of traditional aluminum alloys is low and it is difficult to meet the requirements of high thermal conductivity. Therefore, the development of high thermal conductivity aluminum alloys has become one of the current research hotspots.
[0003] The thermal conductivity of aluminum alloys is closely related to their lattice structure. The solid solution elements, second phases, impurities and defects in the alloy will distort the lattice, hinder the conduction of electrons and phonons, and thus significantly reduce the thermal conductivity. In the prior art, although high-silicon aluminum alloys can provide higher mechanical properties, due to the high Si solid solution content, the lattice distortion is serious, and the plate-like eutectic Si phase will seriously hinder the movement of electrons, resulting in low thermal conductivity of the alloy. In order to improve the thermal conductivity of high-silicon aluminum alloys, existing research focuses on the simultaneous improvement of mechanical properties and thermal conductivity by spheroidizing the eutectic Si phase, but the process is complicated and the improvement effect is limited.
[0004] On the other hand, although low-silicon or silicon-free aluminum alloys have good thermal conductivity, their mechanical properties are weak and it is difficult to meet the requirements of high-strength applications. Therefore, existing studies have mostly used severe deformation processes, such as rolling and drawing, to improve the strength of low-silicon aluminum alloys, but these methods cannot fully improve their thermal conductivity. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a high thermal conductivity aluminum alloy composite material and a preparation method thereof, and the specific scheme is as follows:
[0006] A method for preparing a high thermal conductivity aluminum alloy composite material, the preparation method comprising the following steps:
[0007] S1. Prepare raw materials: select low silicon aluminum alloy as the matrix material, add graphite sheets as reinforcement material, and add rare earth elements;
[0008] S2: Activate the graphite surface;
[0009] S3: mechanically mixing the surface treated graphite flakes and aluminum alloy powder in proportion by ball milling;
[0010] S4: melting and casting the mixed materials, controlling the melting temperature at 680-720° C., and adding rare earth elements during the melting process;
[0011] S5: semi-solid forming process is used for casting, the forming temperature is controlled at 10-15°C below the liquidus temperature of the aluminum alloy, and Mg element is added;
[0012] S6: Heat treatment of castings: Solution treatment and aging treatment of castings.
[0013] Furthermore, the activation of the graphite surface in S2 also includes the following sub-steps:
[0014] S201: soaking the graphite sheet in a 5% sulfuric acid solution for 30 to 60 minutes to remove surface impurities and increase surface roughness;
[0015] S202: Rinse the treated graphite sheet with deionized water to ensure that the sulfuric acid remaining on the surface is removed. The rinsing time is 5 minutes;
[0016] S203: placing the cleaned graphite sheet in an oven at 80° C. to dry for 1 hour;
[0017] S204: soaking the dried graphite sheet in a 1% silane coupling agent solution for 60 minutes to improve the interface bonding strength between the graphite and the aluminum alloy substrate;
[0018] S205: Rinse again with deionized water for 5 minutes, and then dry at 100° C. for 1 hour.
[0019] Furthermore, the parameters of the solution treatment in S6 are: heating the casting to 490-510°C, keeping it warm for 1-2 hours, and then rapidly water cooling it, with the water cooling time not exceeding 30s; the parameters of the aging treatment are: adopting a two-stage aging process, with the first-stage aging temperature at 160°C and keeping it warm for 6 hours; the second-stage aging temperature at 120°C and keeping it warm for 8 hours.
[0020] Furthermore, the S5 further includes the following sub-steps:
[0021] S501: During the semi-solid forming process, the temperature of the aluminum alloy melt is controlled to be 645-655°C;
[0022] S502: Perform mechanical stirring at a speed of 100 to 200 rpm for 5 to 10 minutes to ensure that the reinforcing material is evenly distributed in the matrix;
[0023] S503: Preheat the mold to 200-300°C to reduce the temperature difference between the casting and the mold;
[0024] S504: slowly pouring the semi-solid aluminum alloy melt into the preheated mold at a speed of 2 to 5 m / s;
[0025] S505: After pouring, the casting is naturally cooled at room temperature for 1 to 3 hours, and demolding is performed after cooling.
[0026] Furthermore, the parameters of ball milling mixing in S3 are: ball milling time is 2 to 4 hours; ball milling speed is controlled at 200 to 300 rpm; and ball to material ratio is 10:1.
[0027] Furthermore, the particle size of the graphite flakes in S1 is 10 to 50 μm, and the content is 5 to 30%.
[0028] Furthermore, during the S4 casting, the mechanical stirring speed is controlled at 200-300 rpm, and the stirring time is 20-40 minutes.
[0029] Furthermore, the addition amount of Mg element is 0.5-1.5wt% of the weight of the base aluminum alloy.
[0030] A method for preparing a high thermal conductive aluminum alloy composite material obtains an aluminum alloy composite material.
[0031] Beneficial effects:
[0032] The present invention provides a method for preparing a high thermal conductivity aluminum alloy composite material, which has the following beneficial effects:
[0033] (1) By introducing graphite sheets as reinforcement materials and adding rare earth elements, the thermal conductivity of the material is greatly improved. Compared with traditional aluminum alloys, the thermal conductivity is increased by about 25%-30%, making the material have better performance in application scenarios that require efficient heat dissipation.
[0034] (2) The synergistic effect of graphite flakes and rare earth elements significantly improves the tensile strength and yield strength of the material. In particular, after the interface bonding strength between graphite and aluminum alloy matrix is improved through a special surface treatment process, the comprehensive mechanical properties of the material are greatly enhanced.
[0035] (3) Ball milling is used for mechanical mixing to ensure uniform distribution of the reinforcement phase in the matrix material. At the same time, by optimizing the melting and semi-solid forming process, the fluidity and solidification process of the material are effectively controlled, casting defects are reduced, and processing performance and yield are improved.
[0036] (4) The activation treatment of graphite surface by silane coupling agent significantly improves the interfacial bonding strength between graphite and aluminum alloy matrix, avoids the separation and agglomeration of reinforcement phase, and ensures the structural stability and long-term reliability of the material. DETAILED DESCRIPTION
[0037] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.
[0038] Embodiment 1:
[0039] S1: Prepare raw materials
[0040] Low silicon aluminum alloy AA7075 was selected as the matrix material, and graphite flakes with an average particle size of 20 μm were added, and the graphite content was 10% of the total weight of the matrix. In addition, 0.08 wt% of rare earth element Ce was added.
[0041] S2: Graphite surface activation
[0042] S201: The graphite sheet is immersed in a sulfuric acid solution with a concentration of 5% for 45 minutes to remove surface impurities and increase surface roughness.
[0043] S202: Rinse the treated graphite sheet with deionized water for 5 minutes to ensure that the sulfuric acid remaining on the surface is removed.
[0044] S203: Place the cleaned graphite sheet in an oven at 80° C. and dry for 1 hour.
[0045] S204: soaking the dried graphite sheet in a 1% silane coupling agent solution for 60 minutes to improve the interface bonding strength between the graphite and the aluminum alloy substrate.
[0046] S205: Rinse again with deionized water for 5 minutes, and then dry at 100° C. for 1 hour.
[0047] S3: Mechanical mixing
[0048] The surface treated graphite sheets and aluminum alloy powder were mechanically mixed in proportion and mixed by ball milling: the ball milling time was 3 hours; the ball milling speed was 250 rpm; and the ball-to-material ratio was 10:1.
[0049] S4: Melting
[0050] The mixed materials were melted at a temperature of 700°C, and rare earth element Ce was added during the melting process. The mechanical stirring speed was controlled at 250 rpm for 30 minutes to ensure uniform distribution of the materials.
[0051] S5: Semi-solid forming
[0052] The casting temperature is controlled at 650°C (15°C below the liquidus temperature);
[0053] 1 wt% of Mg element was added and stirred at a speed of 150 rpm for 8 minutes; the mold was preheated to 250° C., the pouring speed was controlled at 3 m / s, and the mold was demolded after natural cooling for 2 hours.
[0054] S6: Heat treatment solution treatment: heating to 500°C, keeping warm for 1.5 hours, followed by rapid water cooling (completed within 20 seconds); aging treatment: primary aging temperature is 160°C, keeping warm for 6 hours; secondary aging temperature is 120°C, keeping warm for 8 hours.
[0055] Embodiment 2:
[0056] S1: Prepare raw materials
[0057] Low silicon aluminum alloy AA5083 was selected as the matrix material, graphite flakes with an average particle size of 30 μm were added, the graphite content was 15% of the total weight of the matrix, and the rare earth element was 0.05wt% La.
[0058] S2: Graphite surface activation
[0059] S201: treating the graphite sheet in a 5% sulfuric acid solution for 60 minutes;
[0060] S202: rinse with deionized water for 5 minutes;
[0061] S203: drying in an oven at 80° C. for 1 hour;
[0062] S204: Soak in 1% silane coupling agent solution for 60 minutes;
[0063] S205: Rinse again with deionized water for 5 minutes and dry at 100° C. for 1 hour.
[0064] S3: Mechanical mixing
[0065] The ball milling time was 2 hours; the ball milling speed was 200 rpm; and the ball-to-material ratio was 10:1.
[0066] S4: Melting
[0067] The melting temperature was controlled at 690°C, and rare earth element La was added. The stirring speed was 220 rpm for 25 minutes.
[0068] S5: Semi-solid forming
[0069] The molding temperature is 655°C (10°C below the liquidus temperature);
[0070] 0.8 wt% of Mg element was added, and the stirring speed was 180 rpm for 6 minutes;
[0071] The mold was preheated to 200°C, the pouring speed was 4 m / s, and demoulding was performed after cooling for 3 hours.
[0072] S6: Heat treatment
[0073] Solution treatment: 495°C, hold for 2 hours, rapid water cooling (completed within 25 seconds);
[0074] Aging treatment: first stage at 160℃ for 6 hours, second stage at 120℃ for 8 hours.
[0075] Embodiment 3:
[0076] S1: Prepare raw materials
[0077] Low silicon aluminum alloy AA6061 was selected as the matrix material, graphite flakes with a particle size of 50 μm were added, the graphite content was 20% of the total weight of the matrix, and the rare earth element was 0.1wt% of Ce.
[0078] S2: Graphite surface activation
[0079] S201: treated in 5% sulfuric acid solution for 30 minutes;
[0080] S202: rinse with deionized water for 5 minutes;
[0081] S203: drying at 80°C for 1 hour;
[0082] S204: Soak in 1% silane coupling agent solution for 60 minutes;
[0083] S205: Rinse again with deionized water for 5 minutes, and then dry at 100° C. for 1 hour.
[0084] S3: Mechanical mixing
[0085] The ball milling time was 4 hours; the ball milling speed was 300 rpm; the ball to material ratio was 10:1.
[0086] S4: Melting
[0087] The melting temperature was 710°C, rare earth element Ce was added, the mechanical stirring speed was 300 rpm, and the stirring time was 40 minutes.
[0088] S5: Semi-solid forming
[0089] The molding temperature is 650°C (15°C lower than the liquidus temperature); 2wt% Mg element is added, and the stirring speed is 50rpm for 10 minutes; the mold is preheated to 300°C, the pouring speed is 2m / s, and demolding is performed after natural cooling for 1 hour.
[0090] S6: Heat treatment
[0091] Solution treatment at 510°C, holding for 1 hour, rapid water cooling (completed within 30 seconds);
[0092] Aging treatment: first stage at 160℃ for 6 hours, second stage at 120℃ for 8 hours.
[0093] The performance of Examples 1-3 and conventional aluminum alloys was tested, and the test data are as follows:
[0094]
[0095] Thermal conductivity: The thermal conductivity of the conventional aluminum alloy is 150 W / m·K, which is significantly lower than the high thermal conductivity aluminum alloy composite material in the embodiment.
[0096] Tensile strength and yield strength: The tensile strength and yield strength of traditional aluminum alloys are low, indicating that their mechanical properties are inferior to those of improved composite materials.
[0097] Elongation at break: Although traditional aluminum alloys have a slight advantage in elongation at break, their overall performance is still inferior to high thermal conductivity aluminum alloy composites with added graphite and rare earth elements.
[0098] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity aluminum alloy composite material, characterized in that: The preparation method comprises the following steps: S1. Prepare raw materials: select low silicon aluminum alloy as the matrix material, add graphite sheets as reinforcement material, and add rare earth elements; S2: Activate the graphite surface; S3: mechanically mixing the surface treated graphite flakes and aluminum alloy powder in proportion by ball milling; S4: melting and casting the mixed materials, controlling the melting temperature at 680-720° C., and adding rare earth elements during the melting process; S5: semi-solid forming process is used for casting, the forming temperature is controlled at 10-15°C below the liquidus temperature of the aluminum alloy, and Mg element is added; S6: Heat treatment of castings: Solution treatment and aging treatment of castings.
2. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The activation of the graphite surface in S2 also includes the following sub-steps: S201: soaking the graphite sheet in a 5% sulfuric acid solution for 30 to 60 minutes to remove surface impurities and increase surface roughness; S202: Rinse the treated graphite sheet with deionized water to ensure that the sulfuric acid remaining on the surface is removed. The rinsing time is 5 minutes; S203: placing the cleaned graphite sheet in an oven at 80° C. to dry for 1 hour; S204: soaking the dried graphite sheet in a 1% silane coupling agent solution for 60 minutes to improve the interface bonding strength between the graphite and the aluminum alloy substrate; S205: Rinse again with deionized water for 5 minutes, and then dry at 100° C. for 1 hour.
3. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The parameters of the solution treatment in S6 are: heating the casting to 490-510°C, keeping it warm for 1-2 hours, and then rapidly cooling it with water, and the cooling time does not exceed 30s; the parameters of the aging treatment are: adopting a two-stage aging process, the first-stage aging temperature is 160°C, and the temperature is kept for 6 hours; the second-stage aging temperature is 120°C, and the temperature is kept for 8 hours.
4. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The S5 further comprises the following sub-steps: S501: During the semi-solid forming process, the temperature of the aluminum alloy melt is controlled to be 645-655°C; S502: Perform mechanical stirring at a speed of 100 to 200 rpm for 5 to 10 minutes to ensure that the reinforcing material is evenly distributed in the matrix; S503: Preheat the mold to 200-300°C to reduce the temperature difference between the casting and the mold; S504: slowly pouring the semi-solid aluminum alloy melt into the preheated mold at a speed of 2 to 5 m / s; S505: After the pouring is completed, the casting is naturally cooled at room temperature for 1 to 3 hours, and demolding is performed after the cooling is completed.
5. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The parameters of ball milling mixing in S3 are: ball milling time is 2 to 4 hours; ball milling speed is controlled at 200 to 300 rpm; ball to material ratio is 10:
1.
6. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The particle size of the graphite flakes in S1 is 10 to 50 μm, and the content is 5 to 30%.
7. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: During S4 casting, the mechanical stirring speed is controlled at 200-300 rpm, and the stirring time is 20-40 minutes.
8. The method for preparing a high thermal conductivity aluminum alloy composite material according to claim 1, characterized in that: The addition amount of Mg element is 0.5-1.5wt% of the weight of the base aluminum alloy.
9. The aluminum alloy composite material prepared by the preparation method according to any one of claims 1 to 8.